A feasibility study on the improvement of DZUP's programming qith advertising and promotions support - Abad, Ma. Angelica D.; Sevilla, Andres (Quezon City College of Mass Communication, University of the Philippines Diliman, 1992)
"This study was conducted in order to improve the programming format of DZUP with advertising and promotions support based on the preferences of the U.P Community. An audience profile of the present primary target audience of DZUP was drawn up based on a survey with a universe of 100 respondents. The following were the findings derived: (1) The Musical Program was the most preferred program type and that the Mellow Tunes was the most preferred music type (2) the most preferred news and public affairs program was the National news (3) Comedy was the most preferred format for the Drama programs (4) the most preferred Instructional Program type was the Foreign Languages (5) Fairytales were the most preferred format for the Children's Program (6) the most preferred program type for the Cultural Programs was the Folk Songs (7) studies on the Holy Book was the most preferred program type for the Religious Programs (8) Only 48% of the respondents were aware of the existence of DZUP. And out of that percentage, only 22 persons tuned in to DZUP at least once (9) Most of those who tuned in to DZUP only listen for less than an hour with the primary purpose of being informed (10) DZUP's programming adequacy was given a rating of seven (11) DZUP's advertising adequacy was given a rating of two (13) Only 3% knew the location of the DZUP studios. Based on these findings, the researcher highly recommends to tailor the programming format of DZUP to the varying tastes and needs of the U.P community. She also believes that DZUP should first concentrate on improving its current programming format within its broadcasting hours before applying to extend its airtime. DZUP should also embark on an advertising and promotions campaign to support its programming format."
Vita.
Thesis (A.B. Broadcast Communication)--University of the Philippines Diliman